Penerapan Metode Kansei Engineering dalam Inovasi Produk Sabun - Hasibuan , Haddad Alwi Hakim; Harahap, Uun Novalia; Zaharuddin, Zaharuddin; Idris, Muhammad (CV. IRA PUBLISHING, 2025)
To remain competitive, the soap manufacturing industry must understand consumer preferences. This study uses the Kansei Engineering method to explore consumer desires for bar soap, which links user impressions and emotions (Kansei) to product design elements. Thirteen Kansei words were identified and translated into five design items, each with multiple categories. Using orthogonal design in SPSS 24.0, 16 stimuli were generated. Conjoint analysis was then applied to examine the relationship between Kansei words and product attributes. Results revealed the most preferred combination: round shape, white colour, medium size (85g), moisturizing function, and long-lasting fragrance. These findings guide designing bar soap products that better match consumer expectations.